2021
DOI: 10.1016/j.ijscr.2021.106522
|View full text |Cite
|
Sign up to set email alerts
|

The diversity and outcome of post-covid mucormycosis: A case report

Abstract: Introduction and importance The impact of Covid-19 pandemic on the incidence and pattern of Mucormycosis (the black fungus), has increased sharply and is featured as an epidemic within a pandemic. The majority of cases were detected at late stages, which decreases the chances of survival. Case presentation The authors present a case of an immunocompetent male patient diagnosed with left orbital apex syndrome post covid-19 infection, which necessitated orbital exenterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…They reported that the number of CAM patients were much higher than the numbers presenting in the prior 3 years during equivalent intervals (range, one to two cases), and were much higher than those reported in the literature in different settings in the pre-pandemic era. 32,33,34,35,36 Abdel-Aziz M et al, 2022 reported 16 new CAM cases in Cairo University Hospitals during the first six months in 2021 which were double the number seen in the same period of the previous year. It showed that all of them were recovered COVID-19 diabetic patients, and corticosteroids were included in their treatment protocol.…”
Section: Discussionmentioning
confidence: 95%
“…They reported that the number of CAM patients were much higher than the numbers presenting in the prior 3 years during equivalent intervals (range, one to two cases), and were much higher than those reported in the literature in different settings in the pre-pandemic era. 32,33,34,35,36 Abdel-Aziz M et al, 2022 reported 16 new CAM cases in Cairo University Hospitals during the first six months in 2021 which were double the number seen in the same period of the previous year. It showed that all of them were recovered COVID-19 diabetic patients, and corticosteroids were included in their treatment protocol.…”
Section: Discussionmentioning
confidence: 95%
“…Fungal rhinosinusitis can be divided into invasive and non-invasive types [8], depending on the potential of the fungal hyphae to invade the tissues through the epithelium (invasive) in comparison with the infection confined to the superficial epithelium (non-invasive) [26]. Invasive fungal rhinosinusitis is a more aggressive form compared with a non-invasive one, which can lead to serious morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…
One of the otorhinolaryngological manifestations of the post-COVID-19 syndrome is rhinosinusitis [6]. The latter is known to be caused by various factors of exogenous and endogenous origin [7], but in patients in post-COVID-19 period, based on literature data, it is caused by fungi [8,9]. The incidence of fungal rhinosinusitis is markedly more prominent in post-COVID19 patients than in non-COVID-19 [9].
…”
mentioning
confidence: 99%
“…The progression of the disease is by direct spread or hematogenous facilitated by angioinvasion [27] . The classical presentation in rhino-orbito-cerebral mucormycosis are nasal crusting, obstruction and swelling, facial pain and paresthesia, headache, and orbital swelling, inflammation, eyelid drooping, and proptosis [28] , [29] , [30] , [31] . In our case the presentation was unusual, she came with diffuse, sever ear pain and facial palsy without any rhino-orbito-cerebral compliant at the time of presentation.…”
Section: Discussionmentioning
confidence: 99%